Synthesis and Bioactivity of Thiazolethioacetamides as Potential Metallo-β-Lactamase Inhibitors - Yi-Lin Zhang; Yong Yan; Xue-Jun Wang; Ke-Wu Yang (MDPI AG, 2020)
Metallo-β-lactamase (MβLs) mediated antibiotic resistance seriously threatens the treatment of bacterial diseases. Recently, we found that thioacetamides can be a potential MβL inhibitor skeleton. In order to improve the information of the skeleton, twelve new thiazolethioacetamides were designed by modifying the aromatic substituent. Biological activity assays identify the thiazolethioacetamides can inhibit ImiS with IC50 values of 0.17 to 0.70 μM. For two of them, the IC50 values against VIM-2 were 2.2 and 19.2 μM, which is lower than in our previous report. Eight of the thiazolethioacetamides are able to restore antibacterial activity of cefazolin against E.coli-ImiS by 2−4 fold. An analysis of the structure−activity relation and molecule docking show that the style and position of electron withdrawing groups in aromatic substituents play a crucial role in the inhibitory activity of thiazolethioacetamides. These results indicate that thiazolethioacetamides can serve as a potential skeleton of MβL inhibitors.